LAN Bandwidth Management Using the Queue Tree Method - Safinatunnaza, Salwa; Noviriandini, Astrid; Indriyani, Luthfi; Fauziah, Sifa (Manunggal Halim Jaya, 2025)
The advancement of technology, particularly in computer networks, has enabled global connectivity through the Internet. Computer networks connecting various devices allow for information sharing and communication. One common issue is slow internet speed due to suboptimal bandwidth utilization. To address this issue, bandwidth management becomes crucial, especially in managing multiple applications at PT. XYZ, bandwidth management is implemented using a Mikrotik router using the Queue Tree method. This method allows for flexible and fair bandwidth allocation, ensuring every device has a stable internet connection. This method helps enhance efficiency and ensures bandwidth allocation is aligned with user needs, resulting in smooth and evenly distributed connectivity across the network.